2016
DOI: 10.5535/arm.2016.40.3.470
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Motor and Somatosensory Evoked Potentials During Spine Surgery: Intraoperative Changes and Postoperative Outcomes

Abstract: ObjectiveTo evaluate whether the combination of muscle motor evoked potentials (mMEPs) and somatosensory evoked potentials (SEPs) measured during spinal surgery can predict immediate and permanent postoperative motor deficits.MethodsmMEP and SEP was monitored in patients undergoing spinal surgery between November 2012 and July 2014. mMEPs were elicited by a train of transcranial electrical stimulation over the motor cortex and recorded from the upper/lower limbs. SEPs were recorded by stimulating the tibial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
1
14
4
Order By: Relevance
“…For postoperative neurologic deterioration, the alert criteria for intraoperative MEP changes vary from 50% to 75% in amplitude reduction [ 4 ]. Some studies included amplitude criterion in addition to the latency criterion for SEP monitoring [ 4 19 20 ]. The specific alarm criteria in our spine hospital are a more than 50% reduction in MEP amplitude, and a more than 10% of N20 or P37 latency prolongation for SEPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For postoperative neurologic deterioration, the alert criteria for intraoperative MEP changes vary from 50% to 75% in amplitude reduction [ 4 ]. Some studies included amplitude criterion in addition to the latency criterion for SEP monitoring [ 4 19 20 ]. The specific alarm criteria in our spine hospital are a more than 50% reduction in MEP amplitude, and a more than 10% of N20 or P37 latency prolongation for SEPs.…”
Section: Discussionmentioning
confidence: 99%
“…This study reconfirms the conclusion of previous studies that the highest reliability can be achieved by performing both MEPs and SEPs simultaneously. In our previous study, we reported only SEP changes predicted persistent motor deterioration in spinal cord tumor surgery, and a combined MEP/SEP monitoring showed high sensitivity and specificity in spinal deformity surgery [ 20 ]. To follow up on our previous study, we now make findings on the different sensitivities and specificities of MEPs and SEPs observed for each type of spinal cord tumor by anatomical and pathological type.…”
Section: Discussionmentioning
confidence: 99%
“…However, SEPs reflect only the functional integrity of the spinal sensory pathway, and there have been reports of postoperative paralysis despite the appearance of intact SEPs ( 7 ). In addition, SEP recording requires a signal averaging process, which results in a time delay while the neurophysiological physician communicates with the surgeon ( 8 ). This lack of real-time feedback prior to intervention may lead to an irreversible spinal cord injury ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 However, many studies have suggested that SEPs do not reflect the specificity of motor pathways, as there are several so-called falsenegative results, i.e., emergence of postoperative motor deficits despite unchanged intraoperative SEPs. 4,5 In addition, SEP deterioration can occur in numerous situations such as dorsal column injury, stimulus failure, and distal conduction block, which may result in amplitude reduction below an arbitrary 50% and can falsely imply motor injury. 6 To date, muscle motor evoked potentials (MEPs) are also monitored.…”
mentioning
confidence: 99%